2022
DOI: 10.3390/children9101450
|View full text |Cite
|
Sign up to set email alerts
|

Human Milk Feeding for Septic Newborn Infants Might Minimize Their Exposure to Ventilation Therapy

Abstract: Background. It has been well established that human milk feeding contributes to limiting lung diseases in vulnerable neonates. The primary aim of this study was to compare the need for mechanical ventilation between human milk-fed neonates with sepsis and formula-fed neonates with sepsis. Methods. All late preterm and full-term infants from a single center with sepsis findings from 2002 to 2017 were identified. Data on infant feeding during hospital admission were also recorded. Multivariate logistic regressio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 34 publications
0
2
1
Order By: Relevance
“…We do not have an explanation for our results on meningitis. Concerning hypotonia, it has been reported that a high proportion of oppy infants also show shallow measurements of muscle strength [11,12], and systematic reviews con rm the positive association between breastfeeding and body strength or balance beyond infancy [13,14]. However, we have found no evidence that human milk feeding in uences muscle tone or strength in newborns prior to our study.…”
Section: Discussioncontrasting
confidence: 66%
“…We do not have an explanation for our results on meningitis. Concerning hypotonia, it has been reported that a high proportion of oppy infants also show shallow measurements of muscle strength [11,12], and systematic reviews con rm the positive association between breastfeeding and body strength or balance beyond infancy [13,14]. However, we have found no evidence that human milk feeding in uences muscle tone or strength in newborns prior to our study.…”
Section: Discussioncontrasting
confidence: 66%
“…During the study period (2002–2017), 4,210 neonates were admitted to the participating NICU, 7.6% ( n = 322; 260 in HM group and 62 in EF group) of whom met inclusion criteria and were eligible to participate in the final analysis. Similar to what was published in an earlier study of these cohorts examining the relationship between type of feeding and type of respiratory support ( 10 ), baseline characteristics of neonates who received any amount of HM and neonates who received only formula are summarized in Table 1 . The mean age of newborns on admission to the neonatal unit was 4.3 days in cases of bacterial sepsis and 12.9 days in cases of viral sepsis, and 20% of infants with bacterial sepsis required vasoactive support compared to 2% of infants with viral sepsis.…”
Section: Resultsmentioning
confidence: 88%
“…This is a secondary analysis of data collected for a doctoral thesis intended to explore the clinical and laboratory characteristics of neonates with viral or bacterial sepsis ( 9 ). Previous research contains complete details of the methodological processes ( 10 ). In brief, this study was carried out using a retrospective review of electronic medical records of late preterm and full-term newborn infants.…”
Section: Methodsmentioning
confidence: 99%